Menumbuhkan generasi emas: Strategi pendidikan anak usia dini di era global - Oktami, Khaisya Nabila (Maliki Interdisciplinary Journal, 2024)
Early childhood education in today's digital era is an important factor that shapes a golden generation ready to face global challenges. This article discusses various educational strategies based on the integration of STEAM or Science, Technology, Engineering, Arts, Mathematics curriculum and character education. All learning processes involve habitual use of technology, and enable children to develop critical, creative and digital literacy skills, without compromising the essence of physical play to support brain optimisation. Technology is a support tool for teachers and parents in educating children to realise their full potential. On the other hand, a holistic education approach that familiarises children with critical and interpersonal thinking is a strong factor in preparing children for global competition. Teachers must be active in the educational process that combines academic skills, basic level coordination, moral development, and social-emotional development of a child. By applying innovative and appropriate educational methods, children will grow into people of character who are ready to face the changing times. Critical skills, creativity and digital literacy are enhanced with technology as a supporting tool, not a substitute for physical activity. Thus, the role of teachers and parents must work together to maximise children's potential.